FUNDAMENTALS OF PREVENTION OF THORACIC ORGAN DISEASES IN MILITARY PERSONNEL (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The article examines contemporary principles for the prevention of thoracic organ diseases among military personnel during active military service. A comprehensive approach is presented, encompassing organizational, medical, and sanitary-hygienic measures aimed at reducing morbidity and preventing complications. Particular emphasis is placed on the early detection of pathology using modern imaging techniques (chest radiography and multislice computed tomography [MSCT]), the prevention of infectious complications in chest trauma, and the avoidance of chronic obstructive pulmonary disease (COPD) development. Key strategies discussed include smoking cessation, vaccination against influenza and pneumococcal infection, physical training, adaptation to climatic and geographic conditions of service, and psychological support for personnel. The critical role of adherence to sanitary-hygienic standards and the integration of advanced diagnostic technologies within the military medical support system is highlighted. The conclusion underscores the necessity of an interdisciplinary and multi-level approach to the prevention of thoracic organ diseases in order to preserve the health and combat readiness of military personnel.